Effect of dry-wet cycles on carbon dioxide release from two different volcanic ash soils in a Japanese temperate forest. Issue 5 (3rd September 2019) - Nagano, Hirohiko; Atarashi-Andoh, Mariko; Koarashi, Jun
ABSTRACT: In the present study, two volcanic ash soils (soil A and B) from a temperate broad-leaved forest in eastern Japan were aerobically incubated under repeated dry-wet cycles and continuously constant moisture conditions. The primary aims were to quantify the potential for enhancement of carbon dioxide (CO2 ) release owing to increased water fluctuation and to examine differences in the responses of volcanic ash soils with different physicochemical properties. Soil B, rather than soil A, was a typical Andosol. During incubation at 20°C for 120 days with five dry-wet cycles, the CO2 release rate was measured periodically. Abundance of the stable carbon isotope in CO2 (δ 13 C-CO2 ) was measured to capture changes in the origin of decomposed soil organic matter (SOM) owing to the dry-wet cycles. The CO2 release rate under the dry-wet cycles was up to 49% higher than the values predicted from a parabolic relationship between CO2 release and water content during incubation under the continuously constant moisture condition. The magnitude of CO2 release enhancement was 2.7-fold higher in soil B relative to that in soil A. The δ 13 C-CO2 value in the dry-wet cycles was enriched by 0.3–2.3‰ compared to that during incubation under the continuously constant moisture conditions, suggesting that the decomposition of well-metabolized and/or old SOM was enhanced by the dry-wet cycles. Thus, the present study suggests that Andosols, which have been believed to have a strong SOM stabilization ability, are vulnerable to dry-wet cycles. Then, increased water fluctuation in a future warmer world would have significant potential to stimulate CO2 release from soils.